Gender Inequality in Economic Participation: A Socio-Economic Analysis in Indonesia - Hayati, Amelia; Fadhilah, Nurul; Yosefina, Maria (PT. Anagata Sembagi Education, 2024)
This research addresses gender inequality in economic participation in Indonesia, an issue that poses a barrier to sustainable development and social equality. Although there has been an increase in women's participation in the economic sector, women's labor participation rate is still significantly lower than men's, with an average labor participation rate of 83-84% for men and only 50-53% for women (BPS, 2018-2023). Various social and structural barriers, including patriarchal culture and the burden of domestic responsibilities, limit women's role in the public sector. This study uses descriptive analysis to evaluate trends and patterns of gender inequality in the Indonesian economy from 2018 to 2023, utilizing data from BPS. The findings show that gender inequality in economic participation disadvantages women and slows national economic growth. With more inclusive policies, Indonesia can correct this imbalance and increase its potential productivity and economic competitiveness.